First record of non-mammalian cynodonts (Therapsida) in the Sanga do Cabral Formation (Early Triassic) of southern Brazil - Abdala, Fernando; Dias-de-Silva, Sergio; Cisneros, Juan C (My University, 2002)
New material from the Sanga do Cabral Formation in southern Brazil is described, including one distal and three proximal portions of femora, and a distal portion of a humerus. Comparative studies indicate affinities of the proximal femora and the distal humerus with non-mammalian cynodonts, whereas the distal femur cannot be attributed with certainty to this group. These postcranial elements are the first record of non-mammalian cynodonts for the Sang a do Cabral Formation and demonstrate the presence of small- to medium-sized representatives of this group in the Early Triassic fauna of Brazil.
Keywords: Triassic; non-mammalian cynodonts; Sanga-do-Cabral Formation; Brazil